Translation directed by hepatitis A virus IRES in the absence of active eIF4F complex and eIF2. - Natalia Redondo; Miguel Angel Sanz; Jutta Steinberger; Tim Skern; Yuri Kusov; Luis Carrasco (PLoS ONE)
Translation directed by several picornavirus IRES elements can usually take place after cleavage of eIF4G by picornavirus proteases 2A(pro) or L(pro). The hepatitis A virus (HAV) IRES is thought to be an exception to this rule because it requires intact eIF4F complex for translation. In line with previous results we report that poliovirus (PV) 2A(pro) strongly blocks protein synthesis directed by HAV IRES. However, in contrast to previous findings we now demonstrate that eIF4G cleavage by foot-and-mouth disease virus (FMDV) L(pro) strongly stimulates HAV IRES-driven translation. Thus, this is the first observation that 2A(pro) and L(pro) exhibit opposite effects to what was previously thought to be the case in HAV IRES. This effect has been observed both in hamster BHK and human hepatoma Huh7 cells. In addition, this stimulation of translation is also observed in cell free systems after addition of purified L(pro). Notably, in presence of this FMDV protease, translation directed by HAV IRES takes place when eIF2α has been inactivated by phosphorylation. Our present findings clearly demonstrate that protein synthesis directed by HAV IRES can occur when eIF4G has been cleaved and after inactivation of eIF2. Therefore, translation directed by HAV IRES without intact eIF4G and active eIF2 is similar to that observed with other picornavirus IRESs.